Pengembangan pembelajaran dengan model discovery learning menggunakan media pembelajaran lectora inspire di SMA pada pokok bahasan ikatan kimia - Fitria, Cindy; Sutiani, Ani (ARKA INSTITUTE, 2022)
This study aims to show the feasibility of using the lectora inspire learning media based on BSNP criteria; show whether the discovery learning model has an effect on learning outcomes; show learning achievements by comparing them to the KKM; and show the correlation between motivation and learning outcomes with the discovery learning model using the lectora inspire learning media. This study uses the ADDIE approach. The research on the implementation stage of using the lectora inspire learning media was conducted with Pre-Experiment Designs in the form of One-Group Pretest-Posttest Design. The sample selection was carried out using the purposive sampling technique, the sample studied was 41 students of SMA Negeri 7 Medan. The results of this study indicate that the average feasibility of using the lectora inspire learning media on all BNSP criteria is in the very feasible category; its use has an effect on improving student learning outcomes; the learning achievement obtained with the discovery learning model using the lectora inspire learning media is higher than the KKM; and student learning motivation is significantly correlated with their learning outcomes. It can be concluded that the lectora inspire media product obtained from this study is an innovative media product.